The Effect of Deoxyfluorination on Intermolecular Interactions in the Crystal Structures of 1,6-Anhydro-2,3-epimino-hexopyranoses - Jakubec, Martin; Císařová, Ivana; Karban, Jindřich; Sýkora, Jan (Molecules (Basel, Switzerland), 2022)
The effect of substitution on intermolecular interactions was investigated in a series of 1,6-anhydro-2,3-epimino-hexopyranoses. The study focused on the qualitative evaluation of intermolecular interactions using DFT calculations and the comparison of molecular arrangements in the crystal lattice. Altogether, ten crystal structures were compared, including two structures of C4-deoxygenated, four C4-deoxyfluorinated and four parent epimino pyranoses. It was found that the substitution of the original hydroxy group by hydrogen or fluorine leads to a weakening of the intermolecular interaction by approximately 4 kcal/mol. The strength of the intermolecular interactions was found to be in the following descending order: hydrogen bonding of hydroxy groups, hydrogen bonding of the amino group, interactions with fluorine and weak electrostatic interactions. The intermolecular interactions that involved fluorine atom were rather weak; however, they were often supported by other weak interactions. The fluorine atom was not able to substitute the role of the hydroxy group in molecular packing and the fluorine atoms interacted only weakly with the hydrogen atoms located at electropositive regions of the carbohydrate molecules. However, the fluorine interaction was not restricted to a single molecule but was spread over at least three other molecules. This feature is a base for similar molecule arrangements in the structures of related compounds, as we found for the C4-Fax and C4-Feq epimines presented here.
Keywords: carbohydrates; epimines; X-ray crystallography; intermolecular interactions; fluorine interactions; deoxyfluorination